2013
DOI: 10.1016/j.jpeds.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Threshold for Improvement in Insulin Sensitivity with Adolescent Weight Loss

Abstract: Objectives To assess the association of weight loss and insulin sensitivity, glucose tolerance, and metabolic syndrome (MS) in obese adolescents following weight loss treatment, and to determine the threshold amount of weight loss required to observe improvements in these measures. Study design A randomized, controlled behavioral weight loss trial was conducted with 113 obese adolescents. Changes in fasting insulin, homeostasis model assessment of insulin resistance (HOMA-IR), whole body insulin sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
11
0
7
Order By: Relevance
“…In the present study, most of the participants in the overweight/obese group showed significant reductions in body mass and fat mass, and their FSI and HOMA-IR were reduced by about 38, and 39%, respectively. In contrast, Abrams et al [ 30 ] reported that a decrease in BMI of 8% was required for improvements in insulin sensitivity in adolescents participating in a 4-month behavioral weight loss trial.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, most of the participants in the overweight/obese group showed significant reductions in body mass and fat mass, and their FSI and HOMA-IR were reduced by about 38, and 39%, respectively. In contrast, Abrams et al [ 30 ] reported that a decrease in BMI of 8% was required for improvements in insulin sensitivity in adolescents participating in a 4-month behavioral weight loss trial.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, weight loss can improve insulin sensitivity in pediatric T2DM. In a randomized controlled trial, an 8% reduction in BMI was associated with improved insulin sensitivity in obese adolescents [ 84 ]. In addition, pediatric T2DM exhibited faster islet β-cell decline and higher rates of treatment failure compared to adult T2DM [ 85 ], and supplementation with Lactobacillus casei strain Shirota fermented milk was found to enhance islet β-cell function in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A two-sample ttest (or the Mann-Whitney test if the primary outcome is not normally distributed) will compare the two arms on mean ΔzBMI. As a secondary analysis, the proportions of children in each arm that achieve a decrease in ΔzBMI of at least 0.25, which is considered to be a threshold for clinically significant weight loss [albeit based on limited data [56][57][58][59];], will be compared. Linear mixed models will be used to investigate the pattern of change in zBMI over time.…”
Section: Analysis Plan 2111 Primary Analysismentioning
confidence: 99%